Investigation Of Signal Degradation Due To Rain On Satellite Downlink At KU-Band For Tropical Climate - Nalinggam, Renuka (2011)
Attenuation due to rain is a major concern in transmission of microwave signals. The effect of rain attenuation is more pronounce when signals are being transmitted at higher frequencies. Many theoretical and experimental studies of rain attenuation have been carried out at temperate regions of the world. In the tropical regions, however, which are famous for heavy rains, the situation is not very encouraging. This is because the data coverage for these regions remains inadequate due to the complex and varying climatic behaviors compared to the temperate regions. Thus, the communication systems in tropical countries is affected unconstructively during the heavy rain season.